PEMBIDANGAN ILMU FIQIH - R, Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2020)
Every Muslim must be aware and at the same time believes that all the activities of his life as a creature of Allah certainly will not be separated from the signs of shari'ah. There are norms that regulate and bind every activity carried out based on detailed propositions. This rule or norm is commonly referred to as jurisprudence. Fiqh is knowledge of Islamic law that is amaliah through detailed arguments. While fiqh scholars define fiqh as a collection of amaliah laws which are required by Islam. Fiqh with that meaning is the fiqh that we find in religious practices or Muslim activities every day. In the science of fiqh, of course there are also fields that must be known to carry out life activities in the world. The purpose of writing to be achieved is to find out the field of jurisprudence, fiqh of worship, and the concept of muamalah in a broad sense. Worship is submission or self-servitude and gratitude for the favor of Allah, Almighty God. While muamalah in a broad sense is the rules of God that must be followed and obeyed in social life to safeguard human interests.